Land Tenure in Oceania - Lundsgaarde, Henry P. (ASAO Monograph Series, 1974)
Discussions of land tenure in social anthropology have usually been deeply embedded in broader empirical and theoretical explanations of social, economic, legal, and political institutions. In this volume the editors have sought to correct the emphasis of previous studies by focusing our attention directly on land tenure in Oceania, without, it must be added, losing sight of the connections between land tenure principles and general social structure. The editors have deliberately looked for similarities by analyzing each tenure system from the same analytical and conceptual perspective. Chapters 1 and 9 specifically discuss the methodological and theoretical framework that evolved in the course of analyzing the seven tenure systems described in chapters 2 through 8. The difficulties and problems encountered by the contributors in presenting their data in comparable form is reflected by the more than three years of analysis, writing, editing, and rewriting necessary to complete this volume. The seven substantive ethnographic chapters illustrate the range and diversity in the land tenure practices which are found within the vast culture area of Oceania. The similarities in basic tenure principles between all seven systems seem all the more remarkable in light of the varied geographical and cultural settings of the seven societies. In all of these societies we find a complete absence of fee simple ownership and a corresponding presence of entailed family estates. The ethnography reveals tenure principles that detail an impressive number and variety of separate categories of property. Each category, in turn, includes an even greater number of rights and duties that symbolize different forms of proprietorship. The differential allocation of these rights and duties among persons and groups represents the exact point of connection between land tenure and social structure. For example, kinship principles that specify the distribution of authority within age, sex, descent, and status categories converge on such tenure principles as land use, land distribution, succession, and inheritance. Principles of political organization concerning the relative scaling of authority and power within the society have clear parallels in the land tenure system, where corporate and individual tenure privileges are differentiated. Economic principles subtly merge with land tenure principles in social domains, where land as a resource and land as a value intersect.